RADICAL ISLAMIC IDEOLOGY IN MAKASSAR: From Dissemination to Politicization (JOURNAL OF INDONESIAN ISLAM, 2011)
This paper is concerned with exploring the dissemination and politization of radical Islamic ideology in Makassar. Little has been done to study this important issue. How did radical ideology develop from time to time in Makassar and how has it evolved to become the political power in the region have gone unnoticed. This paper tries to fill this gap. It assumes that radical ideology is a form of discourse, going through a paradigmatic test in which it was criticized, deconstructed, constructed and reconstructed. The paper is part of the attempts to deconstruct radical ideology by means of dismantling two main factors that have caused it to flourish, the actors and organizations of the ideology. A particular attention is give to the following two issues, in what way the ideology may be regarded as a discourse, and how this discourse is being translated into an ideology. These two specific problems becomes the centre of the analysis together with the process in which they intermingle.